3D collision avoidance system for unmanned aerial vehicle (UAV) with decentralized approach. - Harun, Mohamad Haniff (International Islamic University Malaysia-IIUM, 2023)
Unmanned aerial vehicles UAVs have been developed and refined for decades. Using an integrated software system, autonomous unmanned aerial vehicles (UAVs) perform missions automatically and return to a pre-programmed point. Malaysia has a lot of unoccupied airspace, yet autonomous UAV applications and research are still rare. In critical conditions, autonomous UAVs must deal with a variety of environmental and flight issues. This project involves a decentralized 3D collision avoidance system for an autonomous UAV. Ultrasonic, infrared, and laser rangefinders were chosen for the 3D collision avoidance system. The UAV's obstacle recognition and collision avoidance performance are also tested in four experiments. In various flight conditions, the 3D collision avoidance system can identify several material types and opacities by integrating selected rangefinders. Finally, the 3D collision avoidance system quickly reacts to obstacles in the X, Y, and Z axes.